Renal and Cardiovascular Outcomes of SGLT2 Inhibitors versus ARNI in Cardiorenal Syndrome: A Network Meta-Analysis of Randomized Controlled Trials - Gladian Yanuriska; Taufik Rizkian Asir; Wahyudi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Cardiorenal syndrome involves complex pathophysiological cross-talk between the heart and kidneys, frequently culminating in refractory pulmonary congestion. Two primary pharmacological pillars, Sodium-Glucose Cotransporter-2 inhibitors and Angiotensin Receptor-Neprilysin Inhibitors, independently provide profound cardiovascular and renal benefits. However, direct comparative efficacy remains unquantified, creating clinical dilemmas in therapeutic sequencing. Methods: A systematic review and network meta-analysis were conducted utilizing nine pivotal randomized controlled trials. A frequentist network meta-analysis approach utilizing random-effects models was employed. Time-to-event and continuous outcomes were harmonized and pooled utilizing Standardized Mean Differences to allow for indirect head-to-head comparisons between the two drug classes. Results: The network comprised 43,450 patients. Both therapies significantly reduced cardiovascular events compared to standard care. In indirect comparisons, Angiotensin Receptor-Neprilysin Inhibitors demonstrated a superior reduction in the risk of urgent heart failure hospitalizations (Standardized Mean Difference -0.14; 95 percent Confidence Interval, -0.27 to -0.01) compared to Sodium-Glucose Cotransporter-2 inhibitors. Conversely, regarding the primary composite renal outcome (estimated glomerular filtration rate decline, end-stage renal disease, or renal death), Sodium-Glucose Cotransporter-2 inhibitors exhibited overwhelming statistical superiority over Angiotensin Receptor-Neprilysin Inhibitors (Indirect Standardized Mean Difference -0.35; 95 percent Confidence Interval, -0.50 to -0.20; p<0.001). Conclusion: Both drug classes are indispensable for managing cardiorenal syndrome. Angiotensin Receptor-Neprilysin Inhibitors provide superior acute cardiovascular hemodynamic relief, whereas Sodium-Glucose Cotransporter-2 inhibitors offer unparalleled long-term structural protection of renal function. Tailored therapeutic sequencing must leverage these distinct physiological advantages.